Examining Cybersecurity Factors Affecting the Adoption and Institutionalization of Internet of Things Technologies in Developing Countries - Hakimi, Musawer; Abdul Wajid Fazil; Zainullah Matin (Department of Informatics, Universitas Malikussaleh, 2026)
The Internet of Things promises transformative benefits for developing countries, ranging from fairly mundane efficiency improvements to markedly enhanced service delivery, yet actual adoption and long-term institutionalization remain slow and decidedly uneven, largely because of persistent security challenges. Privacy breaches, weak authentication, network vulnerabilities, and generally low levels of trust repeatedly emerge as decisive barriers, particularly in resource-constrained environments where even small failures can, in fact, undermine confidence quite severely. This study addresses the gap in synthesizing the security determinants that influence both the adoption and the deeper embedding of IoT technologies. A systematic literature review, guided by PRISMA, was conducted across IEEE Xplore, Scopus, Web of Science, SpringerLink, ACM Digital Library, and Taylor & Francis Online, identifying 25 peer-reviewed studies published between 2020 and 2025. Data extraction focused on security determinants, sectoral focus, regional distribution, and adoption patterns, so the analysis would retain a clear and coherent scope. Deductive coding covering privacy, authentication, and network security was combined with inductive themes related to trust and risk perception, and the findings were synthesized through frequency counts, thematic analysis, and cross-tabulation. Results highlight four dominant security clusters: privacy and confidentiality, trust and risk perception, authentication and access control, and network or infrastructure security. Privacy concerns were most frequently reported, followed quite closely by trust, authentication, and network vulnerabilities. Healthcare and education sectors appear most sensitive to privacy, while Asia dominates the evidence base, with Africa and Latin America still underrepresented. The study concludes that security concerns, while sometimes manageable in pilot phases, become critical barriers to scaling and institutionalization, so policymakers must priorities robust governance, trust-building, and capacity development to realize IoT’s potential in developing-country contexts.